Gas dynamics in galaxy clusters and galaxies / Danial Ahmad Ariffin Lee - Danial Ahmad , Ariffin Lee (2020)
This thesis presents the results from a search for Neutral Hydrogen (HI) for the central region of the galaxy clusters A426 and A1367 using a 7m radio telescope. The resulting beam is substantially larger than previous studies, covering the central 2.5–3 Mpc diameter of these clusters. The detection of HI allows the mass of atomic gas associated with the cluster core to be estimated. The HI is not associated with any particular cluster member but present due to ram pressure and tidal stripping or recombination of intracluster gas. Overall results have revealed the presence of a significant mass of atomic hydrogen gas with relatively narrow velocity dispersion in the cores of A426 and A1367. The dynamics and evolution of clusters is highly dependent on the environment around the galaxies themselves. The parameters of these galaxies give an insight into how clusters function. Two spiral galaxies, NGC 1068 and NGC 1097, are used as case studies. Data from the Atacama Large Millimeter/Sub-millimeter Array (ALMA) and Mapping Nearby Galaxies at Apache Point Observatory (MaNGA) were used. The ALMA data uses Carbon Monoxide (CO) to uncover the rotation curves in the inner regions of the spiral galaxies. The rotational velocity of the galaxy proved useful in classifying them. The mass of HI in the A426 cluster was (3.2 + 0.4) x 1010 solar masses, with the A1367 has (1.6 + 0.4) x 1011 solar masses. For A426 and A1367 the detected HI gas is not consistent with the velocity range of the gas-rich spiral galaxies known within each cluster, leaving open the possibility that this cool atomic gas traces the gas cooling out of the intracluster medium in the cores of the cluster.